2017
DOI: 10.1016/j.hpb.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The safety of the early removal of prophylactic drainage after liver resection based solely on predetermined criteria: a propensity score analysis

Abstract: Drain removal on POD 3 based on the volume and bile concentration is safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Most patients were removed from the peritoneal drainage tube 5 days after surgery. There was a report that drain removal on postoperative day 3 was based on the volume and a safe bile concentration, [ 34 ] also suggesting that a drainage volume <102 mL is the only key predictor of spontaneous closure.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients were removed from the peritoneal drainage tube 5 days after surgery. There was a report that drain removal on postoperative day 3 was based on the volume and a safe bile concentration, [ 34 ] also suggesting that a drainage volume <102 mL is the only key predictor of spontaneous closure.…”
Section: Discussionmentioning
confidence: 99%
“…Another group from Japan built upon this concept but took into account drain volume and compared drain bilirubin to serum bilirubin. 12 They found that drain removal on POD 3 was safe if the drainage was <500 ml on that day and if the bilirubin concentration of the drain was less than three times the serum bilirubin concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Other Japanese reports suggest that drain management can be guided by drain volume and bilirubin concentrations. 12,13 Hokuto et al demonstrated that abdominal drains could be removed safely on postoperative day (POD) 3 if the drain bilirubin concentration is less than three times serum bilirubin with a volume of <500 ml on that day. 12 Furthermore, Yamazaki et al established that early drain removal was safe if drain bilirubin concentration was less than 3 mg/dl on POD 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the timing of drain removal on the incidence of retrograde infection should also be considered. Several studies have illustrated the criteria for drain removal after liver resection based on fluid volume and drain fluid bilirubin level, and the time is mainly on post-operative day 3 (11)(12)(13).…”
mentioning
confidence: 99%